Multi-crystal native SAD analysis at 6 keV - Liu, Qun (International Union of Crystallography, 2014)
Anomalous diffraction signals from typical native macromolecules are very weak, frustrating their use in de novo structure determination. Here, native SAD procedures are described to enhance signal to noise in anomalous diffraction by using multiple crystals in combination with synchrotron X-rays at 6 keV. Increased anomalous signals were obtained at 6 keV compared with 7 keV X-ray energy, which was used for previous native SAD analyses. A feasibility test of multi-crystal-based native SAD phasing was performed at 3.2 Å resolution for a known tyrosine protein kinase domain, and real-life applications were made to two novel membrane proteins at about 3.0 Å resolution. The three applications collectively serve to validate the robust feasibility of native SAD phasing at lower energy.